Entrepreneurship education and self-sustenance among National Youth Service Corps members in Ibadan, Nigeria (2022)
The unemployment is at alarming rate in Nigeria especially among the graduates and the youth, despite the country’s huge natural resources. However, the endemic is not peculiar to Nigeria alone, but almost all Sub-Sahara African states. It is indeed a long-standing global issue. This study therefore, advocated for a refocused educational system towards the acquisition of vocational, technical and entrepreneur skills to enhance business ideas among graduates, particularly university learners called corps members in Nigeria. Human Capital Entrepreneurship and Entrepreneur Event theories guided the study. The study adopted the mixed-method design. Two hundred and sixty two National Youth Service Corps (NYSC) members posted to Ibadan, Oyo state in 2019 were selected purposively for the study based on their willingness and consent to participate. Eight resource persons who were doing well and employer of labours in diverse fields were enlisted to give talks on skill acquisition, idea generation, creativity and innovation and entrepreneurship intention. A reliable and validated questionnaire on skill acquisition, ideas generation, creativity and innovation and entrepreneurship intention were pretested and post tested to collect information from corps members before and after training by the resource persons. The training lasted eight weeks, two weeks each for resource person. The study was complemented with 24 corps members for focus group discussions. Quantitative data were analysed using mean, standard deviation and Cochran C test at 0.05 level of significance, while the qualitative data were content-analysed. Skills acquisition (2.13±0.65; 2.75±0.95), business idea generation (2.42±0.71; 2.75±0.85, creativity and innovation (2.65±0.86; 3.05±0.97) and entrepreneurship intention (2.35±0.46; 2.65±0.69) before and after training were high as against the threshold of 2.50. Entrepreneurship education enhanced youth self-sustenance among service corps members in Ibadan, Nigeria through skills acquisition, business idea generation, creativity and innovation and entrepreneurship intention.